Providing Real Estate Services to Provincial Regional Industry - Mukhitdinov Shoxijahon Khudoyar ugli (Genius Journals, 2022)
This article covers the provision of real estate services to the industry of the region and its analysis.
Keywords: Service sectors; correlation analysis method; industry; Providing real estate services